2011
DOI: 10.1016/j.immuni.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

CD8α+ Dendritic Cells Are an Obligate Cellular Entry Point for Productive Infection by Listeria monocytogenes

Abstract: Summary CD8α+ dendritic cells (DCs) prime cytotoxic T lymphocytes during viral infections and produce interleukin-12 in response to pathogens. Although the loss of CD8α+ DCs in Batf3−/− mice increases their susceptibility to several pathogens, we observed that Batf3−/− mice exhibited enhanced resistance to the intracellular bacterium Listeria monocytogenes. In wild-type mice, Listeria organisms, initially located in the splenic marginal zone, migrated to the periarteriolar lymphoid sheath (PALS) where they gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
190
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(208 citation statements)
references
References 51 publications
14
190
1
Order By: Relevance
“…Rac plays a well-established role in the development and function of CD8a + cDCs (23). Despite the critical role of CD8a + cDCs in initiating T cell-mediated immunity, they are also a required entry point for productive Listeria infection (21,35). Thus, Batf3 proteolytic activity in endosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rac plays a well-established role in the development and function of CD8a + cDCs (23). Despite the critical role of CD8a + cDCs in initiating T cell-mediated immunity, they are also a required entry point for productive Listeria infection (21,35). Thus, Batf3 proteolytic activity in endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Tip-DCs are characterized by their ability to produce TNF-a and the enzyme iNOS, which leads to the production of NO (20). Another splenic DC subset, namely CD8a + conventional DCs (cDCs), is responsible for the final resolution of infection against Listeria through the cross-priming of bacterial-derived Ags to specific CD8 + T cells and the subsequent induction of the cytotoxic T cell response (21,22). Interestingly, Ag cross-presentation in DCs requires endosomal alkalinization through reactive oxygen species (ROS) production resulting from NADPH oxidase (NOX) 2 recruitment, a process dependent on the small GTPase Rac (23)(24)(25).…”
mentioning
confidence: 99%
“…Both transcription factors are essential for the development of splenic CD8a + DCs and their equivalent CD103 + DCs in the periphery (13,20,21). Batf3-deficient mice have been studied intensively; their in vivo CD8 + T cell responses against virus, bacteria, parasites, and tumors are severely impaired (22)(23)(24). Ablation of splenic CD8a + DCs can also be achieved by injection of a proapoptotic reagent, cytochrome C. Cytochrome C-injected mice show impairment of CD8 + T cell responses against soluble or cell-associated Ags and subsequent immunity to tumor challenge (25).…”
mentioning
confidence: 99%
“…These findings clearly indicate that DCs and macrophages need to collaborate with each other for the optimal induction of T cellmediated immune response during Lm infection. Notably, although DCs mediate T cell responses against Lm infection, Edelson et al 36 recently reported that DCs are required for Lm transport, and DC ablation drastically reduces Lm replication. Such different role of DCs probably strengthens the idea that DCs cooperate with macrophages against Lm infection.…”
Section: Microparticles Transfer Lm Antigenmentioning
confidence: 99%